PENGARUH KEBIASAAN MENONTON YOUTUBE TERHADAP PENGUASAAN KOSA KATA ANAK USIA DINI PADA KELOMPOK A DI TK GITA NUSA - Iklilah Dini Fajriyah; Firman Ashadi; Mochammad Maulana Trianggono; Nurhafit Kurniawan (PENDIDIKAN SAINS DAN TEKNOLOGI, 2023)
Youtube is a video service provider platform that is most often used by the public as a medium of entertainment, including early childhood. This study aims to analyse the effect of Youtube viewing habits on children's vocabulary mastery. This research was conducted using a qualitative research approach. The data collection techniques used include observation, interviews and documentation. Research data sources were obtained from group A students as the main focus, student guardians and class teachers as supporting data sources. The results of observations taken in the form of recapitulation of children's vocabulary data in accordance with vocabulary acquisition indicators are analysed descriptively. During the observation, it was seen that children were able to pronounce some standard and formal words that had not even been taught at school. The habit of watching Youtube with genres that are not suitable for children will have a negative impact on the pronunciation of words that are not good, such as impolite words or even dirty words. In this study, it was found that the habit of watching Youtube has an effect on the mastery of vocabulary in early childhood, both positive effects, namely children have a lot of new vocabulary that has a good language structure and diction selection, and negative effects, namely children bring up words that are less polite or not good. The type of Youtube viewing, supervision and guidance from parents affect the mastery of vocabulary in early childhood